Determinan Taxpayer Compliance dengan Understanding of taxation rules Sebagai Variable Moderasi - Muhammad Faris Zharfan; Siti Hartinah (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study aims to analyze the effect of tax system modernization, tax socialization activities, and tax services on taxpayer compliance, with understanding of taxation rules as a moderating variable. The study was conducted on taxpayers registered at the Pondok Aren Tax Office (KPP) in South Tangerang. The research method used was a quantitative approach with data collection techniques through questionnaires and analyzed using Partial Least Square - Structural Equation Modeling (PLS-SEM). The results showed that the modernization of the taxation system had a positive effect on taxpayer compliance, while taxation socialization activities and fiscal services had no effect on taxpayer compliance. In addition, understanding of taxation rules was found to have a significant effect on taxpayer compliance, but was not able to moderate the relationship between modernization of the taxation system, taxation socialization activities, and fiscal services with taxpayer compliance. These findings indicate that increasing taxpayers' understanding of taxation regulations can strengthen compliance levels. This study is expected to contribute to the development of taxation literature and serve as a consideration for tax authorities in formulating strategies to improve taxpayer compliance.